Geomicrobiological Heterogeneity of Lithic Habitats in the Extreme Environment of Antarctic Nunataks: A Potential Early Mars Analog - Fernández-Martínez, Miguel Ángel; García-Villadangos, Miriam; Moreno-Paz, Mercedes; Gangloff, Valentin; Carrizo, Daniel; Blanco, Yolanda; González, Sergi; Sánchez-García, Laura; Prieto-Ballesteros, Olga; Altshuler, Ianina; Whyte, Lyle G.; Parro, Victor; et al. (Frontiers in Microbiology, 2021)
Nunataks are permanent ice-free rocky peaks that project above ice caps in polar regions, thus being exposed to extreme climatic conditions throughout the year. They undergo extremely low temperatures and scarcity of liquid water in winter, while receiving high incident and reflected (albedo) UVA-B radiation in summer. Here, we investigate the geomicrobiology of the permanently exposed lithic substrates of nunataks from Livingston Island (South Shetlands, Antarctic Peninsula), with focus on prokaryotic community structure and their main metabolic traits. Contrarily to first hypothesis, an extensive sampling based on different gradients and multianalytical approaches demonstrated significant differences for most geomicrobiological parameters between the bedrock, soil and loose rock substrates, which overlapped any other regional variation. Brevibacillus genus dominated on bedrock and soil substrates, while loose rocks contained a diverse microbial community, including Actinobacteria, Alphaproteobacteria and abundant Cyanobacteria inhabiting the milder and diverse microhabitats within. Archaea, a domain never described before in similar Antarctic environments, were also consistently found in the three substrates, but being more abundant and potentially more active in soils. Stable isotopic ratios of total carbon (δ 13C) and nitrogen (δ 15N), soluble anions concentrations, and the detection of proteins involved in key metabolisms via the of Life Detector Chip (LDChip), suggest that microbial primary production has a pivotal role in nutrient cycling at these exposed areas with limited deposition of nutrients. Detection of stress-resistance proteins, such as molecular chaperons, suggest microbial molecular adaptation mechanisms to cope with these harsh conditions. Since early Mars may have encompassed analogous environmental conditions as the ones found in these Antarctic nunataks, our study also contributes to the understanding of the metabolic features and biomarker profiles of a potential martian microbiota, as well as the use of LDChip in future life detection missions.